A Case Study Of The Strategic Change For A Local Payment Solution Company As Evolving Into A Regional Player - Pui, Siew Foon (2007)
Malaysia managed to reduce the payment fraud dramatically after the implementation of nationwide Europay-MasterCard-Visa(EMV) Projects in mid-2005. As for today, all credit cards in Malaysia carry EMV chip and there are 61,000 chip-based activated Pointof Sale (POS) devices or called Electronic Draft Capture (EDC) terminals.